(untitled) (World Bulletin of Education and Learning, 2025)
This work highlights the content, principles, and practical approaches to using differentiated teaching technologies for primary school students in an inclusive educational environment. Differentiated instruction involves adapting the learning process to the individual abilities, needs, interests, and learning pace of students. In an inclusive setting, this process becomes especially important, providing opportunities to work effectively with children with disabilities, varying learning speeds, and diverse socio-emotional needs. The study analyzes the advantages of technologies such as adapted tasks, multisensory learning, small group work, step-by-step scaffolding, and alternative assessment. It also emphasizes the teacher’s role in implementing an individual approach in an inclusive environment, as well as the importance of collaboration and communication.